2018
DOI: 10.1111/ijfs.13884
|View full text |Cite
|
Sign up to set email alerts
|

The effect of litchi juice on exopolysaccharide production in milk fermented by Lactobacillus casei

Abstract: Summary In this paper, Lactobacillus casei growth, sugar utilisation, exopolysaccharides (EPSs) formation and EPSs characterisation during fermentation of milk with or without litchi juice were evaluated. During L. casei fermentation of litchi‐milk samples, the EPSs content increased with the increase of litchi juice levels (0–25%, v/v), and the both relationship appeared in S‐type curve. The viscosity of fermented milk also significantly increased with the formation of EPSs, and which positively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…As the shear rate continued to increase, the molecular motion within the yogurt gradually formed the optimal orientation and the apparent viscosity stabilized (Gharaie et al., 2019). At the same shear rate, the apparent viscosity of soy materials‐based yogurt changed in the following order: B > A > C > E > H > I > G > J > F > D. The reason was that L. paracasei could produce a large number of extracellular polysaccharides during the fermentation process, which eventually led to a maximum apparent viscosity, which was consistent with the results of a previous study (Yu et al., 2018).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As the shear rate continued to increase, the molecular motion within the yogurt gradually formed the optimal orientation and the apparent viscosity stabilized (Gharaie et al., 2019). At the same shear rate, the apparent viscosity of soy materials‐based yogurt changed in the following order: B > A > C > E > H > I > G > J > F > D. The reason was that L. paracasei could produce a large number of extracellular polysaccharides during the fermentation process, which eventually led to a maximum apparent viscosity, which was consistent with the results of a previous study (Yu et al., 2018).…”
Section: Resultssupporting
confidence: 90%
“…The reason was that L. paracasei could produce a large number of extracellular polysaccharides during the fermentation process, which eventually led to a maximum apparent viscosity, which was consistent with the results of a previous study (Yu et al, 2018).…”
Section: Rheological Properties Analysis Of Yogurt Fermented By Diffe...supporting
confidence: 89%
“…The presence of starch may have masked changes in the content of total soluble solids in fermented dairy beverage FB. The decrease in the content of soluble solids in fermented dairy beverage FC may be related to the viability of the microorganism, as shown by Yu et al [41], where the authors found that when preparing a dairy beverage with the addition of L. casei, the sucrose and lactose content present in the beverage decreased as the fermentation time increased, demonstrating that the microorganism remained viable during storage, and directly reflecting the decrease in the content of soluble solids and pH, and the increase in the titratable acidity.…”
Section: Evaluation Of Stability Of Physical-chemical and Microbiolog...mentioning
confidence: 86%
“…The viscosity of the sample also increased significantly. Thus, the use of litchi juice in the technology of fermented milk products can accelerate the fermentation process [9]. However, the authors did not study the effect of litchi juice on the mineral composition of a sour-milk dessert.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Thus, the strength of the structure, moisture state, fermentation process, maturation, and composition of dairy products are examined by IR-spectroscopy. The location of the absorption bands of IR-spectra and their intensity determine the nature of atomic groups that are part of the macromolecules of the product [7][8][9][10][11].…”
Section: Determining the Mineral Composition Of The Sour-milk Product With Plant-based Fillersmentioning
confidence: 99%